Glasses in D'Orbigny angrite - Varela, Maria Eugenia (2003)
The angrites are a small and heterogeneous group of achondritic meteorites with highly unusual chemical and mineralogical features. The abundant presence of glasses in D'Orbigny makes this rock a unique member of the angrite group. Glasses fill open spaces, form pockets, and occur as inclusions in olivines. Their physical settings exclude an incorporation from an external source. Major and trace element (rare earth elements [REE], Li, B, Be, transition elements, N and C) contents of these glasses and host olivines were measured combining laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS), secondary-ion mass spectrometry (SIMS), Nuclear Reaction Analysis (NRA), and EMP techniques. Based on the major element composition, glasses filling voids could represent either a melt formed by melting an angritic rock or a melt from which angrites could have crystallized. Trace element contents of these glasses strongly indicate a direct link to the D'Orbigny bulk meteorite. They are incompatible with the formation of the glasses by partial melting of a chondritic source rock or by shock melting. The refractory elements (e.g., Al, Ti, Ca) have about 10 × CI abundances with CaO/TiO2 and FeO/MnO ratios being approximately chondritic. Trace element abundances in the glasses appear to be governed by volatility and suggest that the refractory elements in the source had chondritic relative abundances. Although the glasses (and the whole rock) lack volatile elements such as Na and K, they are rich in some moderately volatile elements such as B, V, Mn, Fe (all with close to CI abundances), and Li (about 3–5 × CI). These elements likely were added to the glass in a sub-solidus metasomatic elemental exchange event. We have identified a novel mechanism for alteration of glass and rock compositions based on an exchange of Al and Sc for Fe and other moderately volatile elements in addition to the well-known metasomatic exchange reactions (e.g., Ca-Na and Mg-Fe). Because glass inclusions in olivine were partly shielded from the metasomatic events by the host crystal, their chemical composition is believed to be closer to the original composition than that of any other glasses. The relative trace element abundances in glasses of glass inclusions in olivine and glass pockets are also unfractionated and at the 10 to 20 × CI level. These glasses are chemically similar to the common void-filling glasses but show a much wider compositional variation. Inclusion glasses demonstrate that at least olivine grew with the help of a liquid. In analogy to olivines in carbonaceous chondrites, initial formation could also have been a vapor-liquid-solid condensation process. At that time, the glass had a purely refractory composition. This composition, however, was severely altered by the metasomatic addition of large amounts of FeO and other moderately volatile elements. The presence of volatile elements such as carbon and nitrogen in glasses of glass inclusions is another feature that appears to give these glasses a link with those hosted by olivines of carbonaceous chondrites. All these features point to an origin from a vapor with relative abundances of condensable elements similar to those in the solar nebula.